The Integration of Indonesia’s Capital Market with the Global Economy: Opportunities, Challenges, and Policy Strategies - Mesrani Togatorop; Muhammad Katma; Jeni Anggresa; Jesicha Makdalena; Tia Ananda Putri; Yanti Yanti; Sherly Natalia; Benius Benius (Trending: Jurnal Manajemen dan Ekonomi, 2026)
This study analyzes the degree of integration between Indonesia's capital market and global financial markets in the post-COVID-19 era of economic openness. Using a quantitative approach with panel data from 2015 to 2024, the research identifies correlation patterns between the Jakarta Composite Index (JCI) and major global stock market indices, including the S&P 500, MSCI Emerging Markets, and Nikkei 225. Findings reveal that the correlation between JCI and global indices increased significantly post-2020, reaching an average of 0.68 compared to 0.41 in the preceding period. The study also identifies three primary opportunities arising from this integration: enhanced market liquidity, diversification of the investor base, and broader access to foreign capital. Conversely, four critical challenges are identified: short-term capital flow volatility, rupiah exchange rate vulnerability, dependence on global sentiment, and regulatory gaps relative to international standards. Based on this analysis, five policy strategies are formulated, encompassing the strengthening of macroprudential frameworks, development of hedging instruments, capital market infrastructure modernization, regulatory harmonization with IOSCO standards, and enhancement of domestic investor financial literacy. The implications are relevant for policymakers at OJK, Bank Indonesia, and capital market participants in formulating strategies to navigate global financial market dynamics.